The association of early feeding practices with eating behaviors and maternal indulgent feeding behaviors among Saudi preschoolers - Mosli, Rana H.; Kutbi, Hebah A. (Frontiers in Psychology, 2023)
Evidence from previous work suggest that feeding practices during the first years of life may influence the development of eating behaviors later in childhood. Early feeding practices may also predict later maternal feeding behaviors. Mothers from an Arab/Middle Eastern background may adopt unique early feeding practices. The objective of this study was to examine the association of offering fruit juice and date syrup-milk mixture in a baby bottle during infancy with: 1) Child eating behaviors during preschool years; 2) Maternal indulgent feeding practices during preschool years. Mothers of preschoolers (n=115) completed questions adopted from the Children's Eating Behavior Questionnaire (CEBQ), Child Feeding Questionnaire-Arabic (CFQ-A), as well as questions assessing early feeding practices and demographic characteristics. Unadjusted and adjusted logistic regression models were tested to examine the association of early feeding practices with child eating behaviors and maternal indulgent feeding behaviors. Odds ratios (ORs) and respective 95% confidence intervals (CI) were derived. Adjusting for covariates, children who were ever offered fruit juice in a baby bottle as infants were more likely to have high food responsiveness at preschool, compared to children who were not (OR=2.93, 95% CI=1.16, 7.42). Mothers who reported ever offering fruit juice in a baby bottle when their children were infants were more likely to adopt greater use of food as a reward when their children were at preschool (OR= 3.25, 95% CI= 1.22, 8.68). Early feeding practices are associated with child eating and maternal feeding behaviors later in childhood. Future longitudinal studies are needed to further establish these associations. Findings from this study can help inform community awareness and education programs to prevent maladaptive feeding practices and promote appropriate feeding strategies throughout childhood.